Job Satisfaction and Turnover Intention: The Moderating Effect of Organizational Commitment - Faizah, Erna Nur; Hakim, Adi Lukman; Astuti, Suryani Yuli (Publisher Cv. Inara, 2021)
Profit organizations or companies engaging in the business world are always triggered to create changes in a wide range of aspects, including managerial policies. It is geared to maintain the organizational sustainability and progress. It is also expected that every change can be favorable in producing organizational effectivity and efficiency at once. The present study examines the moderating effect of organizational commitment on the influence of job satisfaction and turnover intention at PT. Bank Rakyat Indonesia, particularly at the Pontianak branch office in West Kalimantan. A survey is conducted on 30 respondents - the employees of the bank, who are requested voluntarily to fill out the Likert – scale questionnaire. The data is analyzed using a moderate regression and descriptive analysis. The finding reveals that organizational commitment has been identified as a moderator on job satisfaction and turnover intention for the employees of PT. Bank Rakyat Indonesia in the Pontianak branch office.